Formação de professores : saberes pedagógicos e tradicionais da etnociência para os anos iniciais em escolas quilombolas - Trindade, Creusa Barbosa dos Santos (2016)
The thesis I present stemmed from the need to explain and understand what terms and meanings of the ethnoscience knowledge expressed in traditional maroon communities connect to the content of natural sciences of primary education curriculum (1 to 5 years). The research subjects were teachers who work in the Faculty of Education of the National Plan of Teacher Training offered by public heis in Para State and teach the subjects: Chemistry, Physics and Biology and Methodology of Teaching Science and teachers in training who worked in schools located in quilombola communities of Castanhal Municipalities and Salvaterra and taught science to the early years of elementary school. The selection of research locus was due to the location of customers, offering classes in the PARFOR Facility Cores investigated and home proximity of the researcher. The method is qualitative and narrative approach. For systematization of data adopted the discursive textual analysis. To elucidate the organization of research Structured thesis on trials. The first is about Motivations, Influences and Contexts Search, in which I narrate my aspirations for the choice of the theme, the crossings and paths of the researcher and science teaching consists of history narrated by myself, about my school life experiences of teaching key to entering the doctoral process route in which I identify moments of the narrative research findings in my student life and teaching of which evidencio the marks of science education in evolutionary way highlighting the participation of teachers who contributed to my training, their knowledge, sayings and teaching concepts, teaching science and content related sciences to the daily lives of learners. In the second test the explicit School Education Theories Quilombo - Knowledge of Tradition (Teeq). In the third trial expressed the theories for Teacher Training Quilombo Education (TFPEQ) from bibliographic references about the teaching and traditional knowledge of ethnoscience as well as the concepts of the research subjects, and shows the interfaces between Pedagogical Knowledge and Traditional in Science teaching; Teacher Training for Primary Education Years Initials. In the fourth test is aboard the legal and pedagogical aspects about the curriculum theories to the quilombo education (TCEQ) in view of the requirement to include the teaching of the history of Africa and of Africans and their contributions to Brazilian society expressed in Law 10,639 / 2003 . In the fifth and final test expose the Methodological Theories of Natural Science Education (Chemistry, Physics and Biology) for Quilombo Education (TMEQ) from the views of respondents and observation of their teaching practices. The results indicate the existence of webs, wefts, knowledge, meanings and terms that bring knowledge of ethnoscience the natural sciences content in the early years of elementary school, through the instruments that guide the training of teachers and their own life experiences and teachers.